A Comparative-Democratic Analysis of Democratic Processes in Arab Countries (Egypt and Saudi Arabia) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The study of contemporary political processes in the Arab East raises at least two main questions related to the development conditions of the countries located in this region. What does the concept of "democracy" mean to them, and to what extent have the ideas derived from this concept become a reality in the Arab world? If, as a result of certain political forces' activities, the democratization of the political structure has taken on specific forms, who are the initiators, and how prepared are they to deepen the changes they have already implemented?A preliminary analysis of the situation in the Arab world allows us to give a positive answer to whether the democratization process has become a reality in the Arab world.